LEGAL PROTECTION POLICYHOLDERS KRESNA LIFE POST CANCELLATION OF BANKRUPTCY VERDICT - Julius Jonathan; Evelyne Djuanda Tanuraharja (Sean Institute, 2023)
The economy in Indonesia is progressing, one of which is sourced from the insurance industry. In Article 246 of the Code of Business Law (KUHD), insurance is an agreement with which an insurer binds himself to an insured by receiving a premium to provide reimbursement to him for a loss, damage, or loss of expected profit that he may suffer due to an insanity event. In the writing of this thesis there are two problems, namely how the legal protection of PT. Kresna Life against policyholders resulting from violations of Article 12 paragraph (1) of Financial Services Authority Regulation (POJK) No. 71/POJK.05/2016 on Insurance Financial Health and Reinsurance Companies and how the Financial Services Authority as a regulator protects policyholders regarding the decision of bankruptcy cancellation by the Supreme Court. This research method is normative juridical. Due to the violation of Article 12 paragraph (1) of Financial Services Authority Regulation (POJK) No. 71/POJK.05/2016 on Financial Health and Insurance Companies by Kresna Life regarding investment management to the detriment of policyholders because they are not fulfilled claims filed. The Financial Services Authority acted by imposing administrative sanctions against Kresna Life. On the other hand, some policyholders apply for bankruptcy related to the non-fulfilment of claims and the cassation rate verdict overturning the bankruptcy ruling is increasingly unclear regarding the ffulfilmentof the insured's rights. The Financial Services Authority (OJK) should be able to intervene in the submission of the bankruptcy application from the beginning by responding in writing related to approving or rejecting the application for bankruptcy as referred to in Article 51 paragraph (3) of Law No. 40 of 2014 on Insurance as a form of protection for policyholders. However, the Financial Services Authority did not take any action in this case.